CD33 splice site genotype was not associated with outcomes of patients receiving the anti-CD33 drug conjugate SGN-CD33A - Stanchina, Michele (J Hematol Oncol, 2019)
We tested whether a single nucleotide polymorphism (SNP) that affects splicing of CD33 predicted response to treatment in adults with acute myeloid leukemia (AML) who received the novel CD33 antibody-drug conjugate SGN-CD33A. This genotype, for the CD33 splice site SNP rs12459419, was not associated with clinical response (30% CR/CRi in both groups), event-free survival, or overall survival.